2021
DOI: 10.3389/fphar.2021.693298
|View full text |Cite
|
Sign up to set email alerts
|

Glycoproteins From Rabdosia japonica var. glaucocalyx Regulate Macrophage Polarization and Alleviate Lipopolysaccharide-Induced Acute Lung Injury in Mice via TLR4/NF-κB Pathway

Abstract: Background and Aims:Rabdosia japonica var. glaucocalyx is a traditional Chinese medicine (TCM) for various inflammatory diseases. This present work aimed to investigate the protective effects of R. japonica var. glaucocalyx glycoproteins on lipopolysaccharide (LPS)-induced acute lung injury (ALI) and the potential mechanism.Methods: Glycoproteins (XPS) were isolated from R. japonica var. glaucocalyx, and homogeneous glycoprotein (XPS5-1) was purified from XPS. ANA-1 cells were used to observe the effect of gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…JAK/STAT1 and TLR4/NF-κB pathways are important mechanisms of M1 macrophage polarization, while STAT6 is mainly related to M2 ( 45 , 46 , 91 ). Through the in vivo and in vitro experiments, Xie et al.…”
Section: The Role Of Macrophage Polarization In Liver Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…JAK/STAT1 and TLR4/NF-κB pathways are important mechanisms of M1 macrophage polarization, while STAT6 is mainly related to M2 ( 45 , 46 , 91 ). Through the in vivo and in vitro experiments, Xie et al.…”
Section: The Role Of Macrophage Polarization In Liver Diseasesmentioning
confidence: 99%
“…JAK/STAT1 and TLR4/NF-kB pathways are important mechanisms of M1 macrophage polarization, while STAT6 is mainly related to M2 (45,46,91). Through the in vivo and in vitro experiments, Xie et al (92) demonstrated that protein interacting with C kinase 1 up-regulated the expression of STAT6 and p38a as well as inhibited the NF-kB signaling pathway, promoting M2 and inhibiting M1 polarization, which reduced the liver injury.…”
Section: Acute Liver Injurymentioning
confidence: 99%
“…Activation of toll‐like receptor 4 (TLR4) on lung macrophages induces the nuclear factor‐κB (NF‐κB) inflammatory signaling pathway through leading to the release of downstream inflammatory cytokines including interleukin‐1β (IL‐1β), IL‐6, and tumor necrosis factor‐α (TNF‐α), ultimately causing severe inflammatory damage to lung (Shi et al, 2020). In particular, emerging evidence showed that the TLR4/NF‐κB pathway also played an important role in ALI via regulating macrophage polarization (L. Wu et al, 2019; Ren et al, 2021; R. Li, Shang et al, 2020). Li et al demonstrated that high mobility group protein 1 (HMGB1) induced polarization of M1 macrophages through TLR4‐mediated NF‐κB signaling pathway to regulate LPS‐induced ALI (J. Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The consistent result was also confirmed by another study, which revealed that a traditional Chinese medicine Rabdosia japonica var. glaucocalyx could regulate macrophage polarization and alleviate LPS‐induced ALI in mice via TLR4/NF‐κB pathway (Ren et al, 2021). The aforementioned studies strongly supported the important role of TLR4/NF‐κB pathway‐mediated macrophage polarization in ALI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation